Dynamics and Regional Features of Agricultural Production. In the Republic of Uzbekistan - Furqat Turakulovich, Rajabov (International Journal of Psychosocial Rehabilitation, 2020)
The article presents a scientific analysis of the dynamics of agricultural production, regional characteristics, and changes in the structure of industries from the time of independence of the Republic of Uzbekistan to the present. Categories of farms that produce agricultural products in the country, their role in agricultural production, as well as characteristics of their development based on statistical data. Also analyzed are changes in the productivity of the main agricultural crops of Uzbekistan: cotton and grain. At the end of the article, priorities for the further development of agricultural production in the Republic of Uzbekistan are identified.